Етнічна політика КНР: виклики та перспективи в контексті глобалізації - Басараб, Вікторія Олександрівна; Basarab, V. O. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Робота присвячена аналізу етнонаціональної політики КНР з урахуванням її багатонаціонального складу та сучасних викликів. Розглянуто механізми реалізації цієї політики, її правові основи, соціокультурні наслідки та міжнародний контекст. Проаналізовано суперечності між законодавчими гарантіями прав меншин і централізованою практикою управління. Особливу увагу приділено ситуації в Сіньцзяні, Тибеті, Внутрішній Монголії та позиції Тайваню. Показано, що в умовах глобалізації етнополітика КНР стає предметом міжнародної критики та формує важливий зовнішньополітичний вимір.

The thesis analyzes the ethnonational policy of the People’s Republic of China, taking into account its multiethnic composition and current challenges. It examines the mechanisms of this policy’s implementation, its legal foundations, sociocultural consequences, and international context. The study highlights the contradictions between legislative guarantees of minority rights and the centralized governance practice. Particular attention is given to the situation in Xinjiang, Tibet, Inner Mongolia, and the case of Taiwan. It is shown that in the context of globalization, China’s ethnic policy increasingly becomes a subject of international criticism and an important element of its foreign policy image.
Ethnic policy of the PRC: challenges and prospects in the context of globalizatio
Керівник: Панасенко Ганна Сергіївна, кандидат політичних наук, доцент кафедри світової політики, дипломатії та туристичного бізнесу
Keywords: SOCIAL SCIENCES::Social sciences::Political science; SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Other social sciences::European research cooperation; SOCIAL SCIENCES::Other social sciences::Public sector research; INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production; INTERDISCIPLINARY RESEARCH AREAS::Ethnicity; HUMANITIES and RELIGION::History and philosophy subjects::Historical cultures; LAW/JURISPRUDENCE; Китайська Народна Республіка; етнонаціональна політика; національні меншини; автономні регіони; Сіньцзян; Тибет; Тайвань; культурна асиміляція; законодавство КНР; права меншин; People's Republic of China; ethnonational policy; national minorities; autonomous regions; Xinjiang; Tibet; Taiwan; cultural assimilation; PRC legislation; minority rights